Incontinentia pigmenti - Hegde Sundeep; Bhat S; Soumya S; Pai D (Wolters Kluwer Medknow Publications, 2006)
Incontinentia pigmenti or Bloch-Sulzberger syndrome, is a rare X linked dominant disorder with characteristic skin, hair, eye, dental and neurological abnormalities commonly affecting females. This article reports the clinical features and management of a 11 year old girl diagnosed with Incontinentia pigmenti.